SISTEM PAKAR UNTUK MENGIDENTIFIKASI PENYAKIT IKAN KOI MENGGUNAKAN METODE FORWARD CHAINING - Tadzkier, Muhammad Asyraf; Saptomo, Wawan Laksito Yuly; Hasbi, Muhammad (STMIK Sinar Nusantara, 2023)
Koi fish is a fish that is widely kept for ornamental fish or cultivated for profit, as well as other ornamental fish, koi are freshwater fish and koi are included in the category of omnivorous animals because in their natural environment koi eat plants and small animals. Just like fish in general, koi can also be infected by disease, especially if the quality of water and feed is not good, it is not uncommon for many novice breeders to have difficulty identifying symptoms and diseases of koi fish which have an impact on the selling price of koi , another problem is not all breeders are actually in sharing about right knowledge and limited time for consultation process related to symptoms and diseases of koi. Therefore, to solve about problems, this application made to make easier for novice breeders to care for their koi, this application is made web-based using PHP and MySQL database. First process of this application is to ask several questions and if all questions have been answered according to what they experience, the results will appear according to the expert breeder.